Aggregate Type Influence on Microstructural Behavior of Concrete Exposed to Elevated Temperature - Belkadi, Ahmed Abderraouf; Kessal, Oussama; Bentalem, Sara; Aggoun, Salima; Amouri, Chahinez; Khouadjia, Mohamed Lyes Kamel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Exposure of concrete to high temperatures affects its mechanical properties by reducing the compressive strength, bending...etc. Factors reducing these properties have been focused on by several studies over the years, producing conflicting results. This article interested an important factor, that is the type of aggregates. For this, an experimental study on the behavior of concrete based on different types of aggregates: calcareous, siliceous and silico-calcareous subjected to high temperatures.
Keywords: types of aggregates; high temperature; compressive strength; microstructure; mercury porosimeter; kruszywo; wysoka temperatura; wytrzymałość na ściskanie; mikrostruktura; porozymetr rtęciowy